Pengaruh Profitabilitas, Likuiditas, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2017-2022 - Nuraghnia, Fina; Ramli, Rosmini (Universitas Batanghari, 2024)
This study seeks to examine the impact of profitability, liquidity, company size, and capital structure on the firm value of food and beverage sub-sector companies listed on the IDX during the period from 2017 to 2022. The research encompasses 89 companies within the food and beverage sub-sector listed on the IDX. From this population, a purposive sampling technique was employed to select the sample, resulting in 15 companies being analyzed in this study. Data analysis was conducted using panel data regression, processed with EViews 10 software. The methods employed are descriptive and inferential quantitative methods. The test results indicate that debt to equity ratio and return on assets do not affect firm value. In contrast, the current ratio positively impacts firm value, while company size negatively impacts firm value.